Response of Temperature-Related Rice Disaster to Different Warming Levels Under an RCP8.5 Emission Scenario in a Major Rice Production Region of China - Luo, Shuangyi; Jiang, Zhihong; Chou, Jieming; Tu, Gang; Wang, Shuyu (Frontiers in Climate, 2022)
Rice is the basic food for about 50% of global population, and feeds 2/3 of Chinese population. Under the influence of global change, extreme weather events appear to be increasing in frequency, duration and intensity. These effects could reduce food production substantially. In the medium to long term the impacts of climate change on food availability are likely to grow. In this work, we focus on the heat-related rice disaster in Northeast China, and Center and East China, where are the major rice production regions. In this study, we firstly defined the rice damage indexes to describe the observed temporal-spatial characters of temperature-related rice disaster. Then based on the historical and future RCP8.5 scenario outputs of regional climate model LMDZ4 driven by 6 CMIP5 global circulation model, we assessed the ability of LMDZ4 to reproduce the characteristic of temperature-related rice damages in both rice production regions, and used the model projection to estimate the future changes of rice damages under various temperature rising ranges of 1.5, 2, 3 and 4℃. The changes of intensity and duration of heat and cold damages indicated that the extent of heat-related damage basically limited in the west of Northeast China for Northeast China, although the occurrence of heat damage generally increases with global warming, particularly under 2℃ threshold and above. For Center and East China, the heat-related rice damage will increase in both coverage, and intensity. The region will also experience the faster increasing rate of heat damage than Northeast China. When global warming reaching 3 and 4℃, almost the whole area of Center and East China will be affected by median heat-related damage, and the probability that a regional heat damage reaching heavy level would be over 50% by the end of 21th century. On the other hand, the influence disastrous impact of cold event that affecting rice yield will minimize in the both regional coverage and duration, although Northeast China the model projection show inter-model variability and larger uncertainty.